(untitled) - Santrock, John W. (Boston, Mass., 2014)
The book covers the psychological development of the human life span and the journey of life each of us takes. The revision of the 10th edition based on the feedback from students and instructors who used former editions
Keywords: Developmental psychology,Tâm lý học phát triển